Didáctica basada en desarrollo sostenible para la educación general básica superior en la Unidad Educativa “Tabacundo”. - Anrango, Elsa M. (2022)
This research aimed to investigate didactics for the promotion of sustainable development of students from eighth to tenth year of higher basic general education. The problems that were identified were mainly misinformation and ignorance about sustainable development; In addition, the lack of participation in the activities carried out in the institution and classes, since students have other interests such as sports, online games, among others. The research had a quantitative approach since it was specifically investigated about sustainable development didactics that are applied in the institution, and those that could be included in classes to teach sustainability; for which, a survey of both knowledge and teachinglearning was applied to acquire information on the didactics carried out in the educational institution. The educational community was aware of the lack of interest that the pandemic caused to students by not being able to socialize and have face-to-face activities; projects and trainings that are carried out in the educational institution; It should be noted that despite this, the curricular ecological projects were carried out from home with the family, thus maintaining harmony, cooperation on the part of parents, teachers and students. Finally, it was possible to conclude that the educational community is a single body to encourage students to be part of sustainable development and with it a good future generation without neglecting meaningful daily learning in our environment, either with their own awareness-raising didactics.